1981
DOI: 10.1111/j.1365-2230.1981.tb02279.x
|View full text |Cite
|
Sign up to set email alerts
|

Trioxsalen baths plus UV-A in the treatment of lichen planus and urticaria pigmentosa

Abstract: Summary Local photochemotherapy with trioxsalen baths and long‐wave ultraviolet radiation (UV‐A) was used in nineteen patients with lichen planus and five patients with urticaria pigmentosa. Widespread papular lichen planus healed totally in all sixteen patients. Hypertrophic lichen planus was more resistant to therapy; two out of three patients recovered completely and in one the result was good. The average total UV‐A dose in papular lichen planus was only 6 J/cm2. In urticaria pigmentosa good results were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In a study by Gonzalez et al (3), oral PUVA treatment of generalized LP initially produced a complete clinical response in five of 10 patients (50%) and a partial clinical response in three (30%) after 28 treatments. Several other studies have also shown bath PUVA to be an effective treatment for LP (4–7). In fact, one of those studies, by Helander et al (7), suggests that bath PUVA may be even more efficacious than oral PUVA for this indication.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Gonzalez et al (3), oral PUVA treatment of generalized LP initially produced a complete clinical response in five of 10 patients (50%) and a partial clinical response in three (30%) after 28 treatments. Several other studies have also shown bath PUVA to be an effective treatment for LP (4–7). In fact, one of those studies, by Helander et al (7), suggests that bath PUVA may be even more efficacious than oral PUVA for this indication.…”
Section: Discussionmentioning
confidence: 98%
“…Basically, all treatment regimens focus on symptom relief by histamine receptor antagonists and other supportive therapies (6). Phototherapy/photochemotherapy treatments have been successfully employed as second-line therapies to treat cutaneous symptoms in mastocytosis patients (7)(8)(9)(10).…”
Section: Resultsmentioning
confidence: 99%
“…The use of bath PUVA for mastocytosis treatment is still debated in literature. V€ a€ at€ ainen et al (10) show improvement of UP using bath PUVA with trioxsalen in five patients, while Godt et al (7) did not find successfully results using bath PUVA with 8-MOP in four UP patients. The noteworthy fact is that in the literature are not described studies that take into account comparative reports of phototherapy/photochemotherapy applied to mastocytosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The method is effective at least in psoriasis [2], in lichen planus and urticaria pigmentosa [6], and also in nodular prurigo [5]. The aim of this investigation was to study the long-term effects of trioxsalen baths and UVA in psoriasis.…”
mentioning
confidence: 99%